Handbook on obsessive-compulsive and related disorders - Phillips, Katharine A.; Stein, Dan J. (American Psychiatric Publishing, a division of American Psychiatric Association, 2015)
This collection of essays discusses the disorders covered in the new DSM-5 chapter on obsessive-compulsive and related disorders (ORCDs).